THE IMPLEMENTATION OF BOURDON WIERSMA METHOD IN DETERMINING DOMINANT FACTOR CAUSING FATIGUE ON THREE WORKSPACE IN FOOD AND DRINK INDUSTRY PT.X - Faris Ihsan, Muhammad
Working activities in PT.X involve some continuous repetitive works and heavy material handling. Consequently, many workers in different work stations suffer work fatigue, such as in warehouse, packing and office area. This disorder is caused by environmental factors as well as heavy workload and personal characteristics, namely working period and sleeping time. Work fatigue in this study is evaluated using CVL calculation, workload measurement based on SNI 7269:2009, questionnaire, and Bourdon Wiersma assessment. The result shows warehouse workers in shift 1 are exposed to a moderate workload with the average of 215.90 + 60.76 kcal/hour, in terms of environmental factors, humidity measurement in packing area for shift 1 results in the humidity level of 59.38 + 2.76%. Humidity threshold value is 65-95%, therefore humidity in such area is categorized unsafe. Chi-square test on the relation between working period and SSRT questionnaire shows a significance value of 0.048 < 0.05 indicating that working period has an influence on work fatigue. Based on logistic regression test between work period and SRRT questionnaire, it can be concluded that working period also serves as the dominant factor causing work fatigue in several areas, such as office, packing shift 2, as well as warehouse shift 1 with R square 74.8% meaning that work period influences work fatigue as many as 74.8%.